Mediated masculinities through the lens of fashion. - Lim, Justina Jayann Hui Jia. (2013)
This study has two research objectives of how men perceive masculinities through fashion images and how they negotiate their self-identity in their everyday life as a result of this perception. I selected images from magazines mainly using Connell’s (2002) multiple masculinities to conduct my interviews with young men in Singapore. I used active audience theory to analyse how the respondents interpret the images and find that most men rejected sexually ambiguous and overly sexualised images. In order to understand the role fashion plays in the construction of masculinities, I used symbolic interactionism to study the dynamics between symbols and social interaction, arguing that fashion is ultimately symbolic and readers are able to read those images because the fashion symbols are familiar. Combining the two theories, I propose that these young men interact with what they see in fashion images and make a decision of how they want to appropriate particular items to construct their own social and gender identity.